Systematics of Ichnanthus hoffmannseggii and allies (Poaceae, Paspaleae) based on molecular and morphological evidence - Silva, Christian; Davidse, Gerrit; Schnadelbach, Alessandra Selbach; de Oliveira, Reyjane Patrícia (Phytotaxa, 2016)
Ichnanthus hoffmannseggii is an annual panicoid grass that occurs in sandy and open areas of Brazil and currently includes I. piresii in its synonymy. However, herbarium and field work led us to question this circumscription. In a previous phylogenetic study, a specimen with morphological affinities to I. hoffmannseggii was recovered as more related to Echinolaena oplismenoides (currently I. oplismenoides). This study aimed to clarify the relationship between I. hoffmannseggii, I. oplismenoides, and I. piresii using molecular and macro- and micromorphological data. We recognize these three taxa as distinct species and provide characters for distinguishing them and related species, including descriptions, comments, illustrations, distribution maps, SEM images of the upper anthecium, and phylogenetic relationships.